An investigation into the fundamentals of trapping and sensing in microstructured photonic crystal fibers - Shinoj Vengalathunadakal Kuttinarayanan (2012)
Ultra sensitive optical manipulation and detection techniques employing specialty fiber optics and tailor made coherent lasers have huge potential in research and development of new generation medical diagnosis systems. Photonic crystal fiber (PCF) is one such specialty fiber that has emerged prominent in recent years and has found to be an efficient medium for sensing or other micro manipulation such as optical trapping or tweezing and promises a noninvasive, non-contact methodology with minimum damage to the living cells. A hollow-core PCF (HC-PCF) can achieve guidance in air by using the Bragg reflection from the periodic fiber cladding structure, and has the potential of being a medium for efficient biosensing application due to the increased light-matter interaction in the hollow-core.